Study of Geobarometers in Pelitic Schists from The Puturge Metamorphites - Gungor, Filiz (Iop Publishing Ltd, 2016)
Pelitic schists from The Puturge metamorphites contain important minerals, such as garnet, biotite, chlorite, kyanite, and staurolite which are used in the determination of degree of metamorphism. Kyanite in metapelites such as staurolite mica schist, stavrolite garnet mica schist, biotite schist and amphibole schist. Kyanite is one from Al2SiO5 polymorphs (andalusite, sillimanite and kyanite). Kyanite is approximately ten percent more dense than the other two, and hence formation of kyanite is favoured by high pressures. The metamorphic petrology uses pressure-temperature conditions during metamorphic events and fluids in metamorphic environment. The geobarometers were used to estimate metamorphic conditions of pelitic schistes in metamorphites. The study of garnet-aluminum silicate-plagioclase-quartz (GASP) barometry has a long history. Compositions of staurolite and garnet in the assemblage in samples were calculated from temperature and pressure changes. The calculated temperatures could be due to conditions of P-H2O < P-total during metamorphism. The equilibrium among staurolite, garnet, quartz and aluminum silicate is only approximately located in pressure-temperature space.
World Multidisciplinary Earth Sciences symposium (WMESS) -- SEP 05-09, 2016 -- Prague, CZECH REPUBLIC
Keywords: Biotite